Effects of Dietary Curcumin on Growth and Digestive Physiology of Seriola dumerili - Yang, Jingru; Hong, Jiawei; Fu, Zhengyi; Ma, Zhenhua (Frontiers in Marine Science, 2022)
In order to understand the effects of dietary curcumin on the growth and digestive performance of Seriola dumerili, this study was conducted under laboratory conditions. The control group was added with 0% curcumin, and two treatment groups were added with 0.01% and 0.02% curcumin, respectively. Fish were fed with experimental diet for 8 weeks. The growth data, growth genes, intestinal digestive enzymes, tissue parameters, and blood lipid-related indicators were measured, and the correlation between digestive indicators, growth gene indicators, and growth characteristic indicators was analyzed. The results showed that the survival rate, visceral ratio, hepatosomatic ratio, and condition factor of Seriola dumerili increased first and then decreased with the increase of curcumin content in feed. The feed conversion ratio of the control group was significantly higher than that of the treatment group. With the increase of curcumin content in feed, lipase and trypsin increased first and then decreased with the increase of curcumin content. Compared with the control group, curcumin significantly increased the muscle thickness and the number of goblet cells of Seriola dumerili. High and low contents of curcumin can reduce the content of serum total cholesterol and triglyceride, and a low dose (0.01%) of curcumin has the strongest lipid-lowering effect. The relative gene expression of IGF1 and IGF2 reached the maximum in the 0.02% treatment group. The results showed that the addition of curcumin in feed could theoretically improve the survival rate, feed efficiency, and other growth characteristics of Seriola dumerili, improve intestinal digestion and structure, promote intestinal health, and reduce blood lipid levels. The best effect was achieved in the 0.01% treatment group. The results of this study provide a theoretical reference for the feasibility of adding curcumin to Seriola dumerili feed in production and realize the optimal proportion of feed additives for this species, which is beneficial to the sustainable development of aquaculture.